(untitled) (University Heart Journal, 2020)
Background:Chronic heart failure (CHF) is the most common and prognostically unfavorable outcome of many diseases of the cardiovascular system. Clinical trials have demonstrated mortality and morbidity benefits of mineralocorticoid receptor antagonists (MRAs) in patients with heart failure. These studies have used either eplerenone or spironolactone as the MRA. Eplerenone is a selective aldosterone antagonist expected to have a lower incidence of hormonal side effects than spironolactone. The present study is designed to compare these two drugs in chronic heart failure patients as no head to head trial between these two drugs is found regarding improvement of systolic function, tolerability and safety. The aim of this study is to compare the effects of eplerenone and spironolactone on LV systolic function in patients with chronic heart failure in a single center. Methods:It was a randomized clinical trial single blind study. A total of 224 cases of chronic heart failure with reduced ejection fraction and NYHA class III or IV were selected by random sampling, from July 2017 to June 2018. Each patient was randomly allocated into either of the two arms, and was continued receiving treatment with either spironolactone (Arm-I) or eplerenone(Arm-II). Each patient was evaluated clinically, biochemically and echocardiographically at the beginning of treatment (baseline) at 1 month and at the end of 6th month. Echocardiography was performed to find out change in left ventricular systolic function. Result: After 6 months of treatment, ejection fraction was found higher in the eplerenonearm (40.3 ± 6.5 versus 38.3 ± 4.6%; P < 0.05). Ejection fraction (EF) changes were 6.2% in eplerenone group and 4.1% in spironolactonearm. A significant reduction in left ventricular end-systolic volume (21.9±2.5 in group I versus 14.9±5.7 in group II; P < 0.05) and left ventricular systolic diameter (48.7±4.0 in arm I versus 45.2±4.9 in arm II; P<0.05) occurred after 6 months of treatment. But no significant differences were observed in left ventricular end-diastolic volume (187.8±37.4 versus 184.5±33.9; P=0.101) and left ventricular diastolic diameter (60.1±4.5 versus 61.0±4.9; P=0.0818) between arms. Assessment of blood pressure six months after treatment shows, systolic blood pressure (SBP) and diastolic blood pressure (DBP) were improved in both arms but difference between two arms were statistically non-significant (p>0.05). Conclusion: In this study, the improvement in systolic function was more in eplerenone arm, which also had fewer adverse side effects when compared to spironolactone arm. So, it can be concluded that eplerenone can be advised in patient with chronic heart failure in addition to other drugs that are used to treat heart failure. University Heart Journal Vol. 16, No. 2, Jul 2020; 65-70